EFEK APLIKASI GEL EKSTRAK KULIT MANGGIS (Garcinia mangostana L.) TERHADAP JUMLAH SEL MAKROFAG PADA PROSES PENYEMBUHAN LUKA GINGIVA (Kajian pada Rattus norvegicus) - , RICCA PRETY SARI, Dr. drg. Dahlia Herawati, SU., Sp.Perio(K). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wound healing aims to restore the structure and function of the injured tissue. In the inflammatory phase, the movement of inflammatory cells such as neutrophils and monocytes into the injured area, and then monocytes into activated macrophages. Macrophages play an important role in phagocytosis, but besides that macrophages are also capable of synthesizing cytokines interleukin-1Î² and TNF-Î± can increase the inflammatory reaction. The purpose of this study was to determine the effect of mangosteen peel extract gel application (Garcinia mangostana L.) on the number of macrophages in the wound healing process of gingival (Studies on Rattus norvegicus). This study was conducted 36 male Rattus norvegicus aged 3 months with weight 200-250 grams. The rats were devided into three groups : treatment group (40% mangosteen peel extract gel), negative control group (CMC-Na 2%), and positive control group (aloclair gel). Rats in each group were injured at lower centralis incisor labial gingival with 2,5 mm diameter of punch biopsy and then apllied application materials twice a day for 5 days, after that its made to the histological samples using hematoxylin eosin staining. Macrophage was measured by counting the number of cell under the light microscope 400 times magnification in 5 fields of view. The result then analyzed by two-way Anova and Post Hoc LSD Test and continued with the Independent Samples T Test. Two-way Anova test results with significance (p<0,05) showed a significant difference in all the independent variables, between applications, and between the time of observation to the number of macrophages. The conclusion of this research is the application of mangosteen peel extract gel (Garcinia mangostana L.) can reduce the number of macrophages in the wound healing process of gingival (Studies on Rattus norvegicus).